1996
DOI: 10.1021/es960359g
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Carbonyl Compounds as Aqueous-Phase Photochemical Sources of Hydrogen Peroxide in Acidic Sulfate Aerosols, Fogs, and Clouds. 1. Non-Phenolic Methoxybenzaldehydes and Methoxyacetophenones with Reductants (Phenols)

Abstract: Non-phenolic aromatic carbonyl compounds (i.e., benzaldehydes and acetophenones not containing an -OH group on the aromatic ring) and various phenols are present in the atmosphere from the combustion of wood and other biomass and probably from the entrainment of terrestrial humic/fulvic substances present in wind-blown soil aerosol. Illumination (313 nm) of aqueous solutions containing a non-phenolic aromatic carbonyl and a given phenol (phenol itself or a substituted phenol):  produces hydrogen peroxide (HOOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(207 citation statements)
references
References 107 publications
12
194
1
Order By: Relevance
“…Photochemical aqueous phase experiments suggest that ring-retaining aromatic oxidation products from phenol and its methoxylated derivates guaiacol and syringol might contribute to aqSOA as they form aromatic dimer products in high yields (near unity, related to the initial aqueous phase concentration) by recombination of phenoxy radicals (Sun et al, 2010). The total aromatic concentrations in these studies (100 µM) resemble those as found from wood smoke markers in winter fog (Sagebiel and Seiber, 1993); however, at other locations much smaller phenol concentrations are generally observed (Anastasio et al, 1997).…”
Section: Aromatic Compoundsmentioning
confidence: 56%
“…Photochemical aqueous phase experiments suggest that ring-retaining aromatic oxidation products from phenol and its methoxylated derivates guaiacol and syringol might contribute to aqSOA as they form aromatic dimer products in high yields (near unity, related to the initial aqueous phase concentration) by recombination of phenoxy radicals (Sun et al, 2010). The total aromatic concentrations in these studies (100 µM) resemble those as found from wood smoke markers in winter fog (Sagebiel and Seiber, 1993); however, at other locations much smaller phenol concentrations are generally observed (Anastasio et al, 1997).…”
Section: Aromatic Compoundsmentioning
confidence: 56%
“…These additional oxidants include singlet molecular oxygen ( 1 O 2 *), excited triplet states of organic compounds, and peroxyl radicals (Faust, 1994;Anastasio et al, 1997). Initial work has shown that 1 O 2 * is indeed formed on illuminated Summit snow and that the corresponding steady-state concentrations are high enough to be a significant sink for electron rich species such as polycyclic aromatic hydrocarbons (McKellar et al, 2005).…”
Section: Oxidant Production and Chemistry In/on Snow And Ice Grainsmentioning
confidence: 99%
“…Taking into account the energy of 3 1NN (E T = 231 kJ mol -1 ) 35 we can argue that, following reaction 4, interaction with molecular oxygen leads to the formation of both the first and the second electronically excited singlet states: O 2 ( 1 ∆ g ) (94 kJ mol -1 ) and O 2 ( 1 Σ g + ) (157 kJ mol -1 ). Quantification of singlet oxygen photoformation via reaction R4 was possible by using FFA as a chemical probe, and we found a formation rate The reaction between 1NN •-and oxygen (R5) resulting in superoxide was proposed by analogy with the corresponding processes that involve species produced upon reduction of the triplet states of aromatic carbonyls 36 The results displayed in figure 4 give clear evidence that the decay of 3 1NN monitored at 620 nm is higher at low pH and in the presence of chloride. At pH 6.5 in aerated solution the 3 1NN lifetime is about 1.8 µs, and it decreases to ~1.0 µs by acidifying the solution to pH 1.1.…”
Section: Effect Of Oxygenmentioning
confidence: 99%